Land, law and people in medieval Scotland - Neville, Cynthia J. (Edinburgh University Press, 2010)
This ambitious book examines the encounter between Gaels and Europeans in Scotland in the central Middle Ages, offering new insights into an important period in the formation of the Scots' national identity. It is based on a close reading of the texts of several thousand charters, indentures, brieves and other written sources that record the business conducted in royal and baronial courts across the length and breadth of the medieval kingdom between 1150 and 1400. Under the broad themes of land, law and people, this book explores how the customs, laws and traditions of the native inhabitants and those of incoming settlers interacted and influenced each other. Drawing on a range of theoretical and methodological approaches, the author places her subject matter firmly within the recent historiography of the British Isles and demonstrates how the experience of Scotland was both similar to, and a distinct manifestation of, a wider process of Europeanisation.